Economic formation of the Vale do Rio Doce: a historical analysis (1940-1970) - Pereira, Camila Amaral; Espindola, Haruf Salmen; Martins, Diego (Universidade Federal Rural do Rio de Janeiro, 2020)
The shift from the railway system to the road system throughout the first part of the XXI century in Minas Gerais (Brazilian State) is the main issue of this research. Alongside with this this article seeks an understanding of the local economy history at time. In that moment takes place a strong convergence of State actions on infrastructure in this region. Historical resources are the methodological focus: newspapers of this time, the journal Cultura Política and documents from the public archive of the Minas Gerais State. The results indicate that the mining logic of the implantation, in the Vale do rio Doce, of the road network accelerated the occupation process, with population growth and urbanization, highlighting the city of Governador Valadares, which became the junction of the railroad network.